Development and validation of bioanalytical assay methods for sildenafil in human plasma - Tesfu, Michael Kidane (University of the Free State, 2004)
Abstract not available
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2004
Keywords: Sildenafil; Pharmakokinetics -- Research; Drugs -- Analysis; Body fluids -- Analysis